Government communication and public acceptance of policies in South Korea - Kim, Dong Young; Shim, Jun Seop (International Review of Public Administration, 2020)
This study examines the structural relationships between government communication and public acceptance through the mediation of components of actionable core drivers of public trust (responsiveness, reliability, integrity, openness, and fairness) and public trust, using data collected from a survey with 3,000 Korean nationals in South Korea. The results of SEM indicate that the proposed research model explains the data appropriately. When the public perceives the government communication more positive, they perceive the government as responsive, reliable, integritous, open, and fair. Further, public’s positive assessment of these five components of actionable core drivers of public trust lead the public to trust the government more. Higher level of public trust means higher level of public acceptance. The results suggest that the public may accept certain government policies through complex cognitive processes from their perception of government communication that affects their trust on the government rather than just from their preference or rational choice on policies.